A taxonomic review and analysis on biomass supply chain design and planning: New trends, methodologies and applications - Mottaghi, Moheb; Bairamzadeh, Samira; Pishvaee, Mir Saman (Industrial crops and products, 2022)
Due to various environmental problems and social impacts caused by biomass supply chains activities such as climate change, increasing energy demand, energy security, and food crisis, on the one hand, and economic issues such as high costs of biomass supply chains logistics activities, and inefficient production of bioenergy products from low-energy density biomass, on the other hand, modeling and optimization of sustainable biomass supply chains have transitioned to a growing area of research in a recent decade. In this perspective, evaluating three aspects of sustainablity, including economic, environmental, and social sustainability, as the main characteristic to review the literature of supply chain design and planning models has been the subject of several review studies, however, modeling and optimization of sustainable biomass supply chains have not been reviewed and analysed so far. To bridge this gap, this paper provides a taxonomic review of biomass to bio-products supply chains design and planning models that evaluate or optimize economic, environmental, and social aspects of sustainability. To this aim, a total number of 178 papers published in scientific journals are categorized and analyzed according to a comprehensive classification framework, including sustainability dimensions, decision level, modeling approach, model characteristic, solution approach, uncertainty modeling approach, and data. Some significant factors ignored in the previous studies such as sustainability aspects, transportation modes, by-products, type of biomass feedstocks, international and governmental factors are considered in this review in order to provide a comprehensive vision for the readers. Finally, the drawbacks and research gaps that have been identified through the literature review are highlighted, and potential directions for future studies are recommended. •A taxonomic review of sustainable biomass supply chain planning is proposed.•126 journal papers related to sustainable biomass supply chain design are reviewed.•A more extensive classification for sustainable biomass supply chain models is employed.•Literature gaps are identified and potential future research directions are presented.